Eleanore of Avignon : a novel - DeLozier, Elizabeth ([New York] : Dutton, 2024)
"Gorgeously drawn, full of captivating historical drama, and rich with unforgettable characters, Eleanore of Avignon is the story of a woman who is unwilling to bend to the limitations her society places upon her when she becomes the unlikely apprentice to the pope's physician at the most challenging and dangerous moment in medieval European history"--
Keywords: Black Death -- Fiction; Midwives -- Fiction; Historical fiction; Novels